Trade union responses towards labour market dualization comparing the impact of the varieties of industrial relations in Germany, Slovenia and Poland - Christine Gerber (Freie Universität Berlin, Center for International Political Economy, 2014)
This paper analyzes the development of trade unions' adaptation strategies towards the new challenge posed by the dualization of national labour markets into a stable core of standard employment and a growing margin of flexible, often precarious employment. On the basis of the controversial discussion surrounding the theory of Varieties of Capitalism (VoC), the main objective is to shed light on the question of how institutional frameworks shape unions' adaptation strategies. By comparing the developments and union strategies in Germany, Poland and Slovenia - identified as traditionally rather coordinated market economies - the paper aims to connect the still much separated debates on Western and Eastern European regional institutional regimes.
urn:nbn:de:101:1-2014120322431
Keywords: 330